Comparative Analysis of NADPH-Cytochrome P450 Reductases From Legumes for Heterologous Production of Triterpenoids in Transgenic Saccharomyces cerevisiae - Istiandari, Pramesti; Yasumoto, Shuhei; Srisawat, Pisanee; Tamura, Keita; Chikugo, Ayaka; Suzuki, Hideyuki; Seki, Hikaru; Fukushima, Ery Odette; Muranaka, Toshiya (Frontiers in Plant Science, 2021)
Triterpenoids are plant specialized metabolites with various pharmacological activities. They are widely distributed in higher plants, such as legumes. Because of their low accumulation in plants, there is a need for improving triterpenoid production. Cytochrome P450 monooxygenases (CYPs) play critical roles in the structural diversification of triterpenoids. To perform site-specific oxidations, CYPs require the electrons that are transferred by NADPH-cytochrome P450 reductase (CPR). Plants possess two main CPR classes, class I and class II. CPR classes I and II have been reported to be responsible for primary and specialized (secondary) metabolism, respectively. In this study, we first analyzed the CPR expression level of three legumes species, Medicago truncatula, Lotus japonicus, and Glycyrrhiza uralensis, showing that the expression level of CPR class I was lower and more stable, while that of CPR class II was higher in almost all the samples. We then co-expressed different combinations of CYP716As and CYP72As with different CPR classes from these three legumes in transgenic yeast. We found that CYP716As worked better with CPR-I from the same species, while CYP72As worked better with any CPR-IIs. Using engineered yeast strains, CYP88D6 paired with class II GuCPR produced the highest level of 11-oxo-β-amyrin, the important precursor of high-value metabolites glycyrrhizin. This study provides insight into co-expressing genes from legumes for heterologous production of triterpenoids in yeast.